Parental educational attainment and offspring subjective well-being and self-beliefs in older adulthood. (1st July 2018) - Sutin, Angelina R.; Stephan, Yannick; Terracciano, Antonio
Abstract: This research examines whether parental educational attainment and subjective childhood socioeconomic status (SES) is associated with adult offspring well-being and self-beliefs (broadly defined). Participants from the Health and Retirement Study were included if they completed the leave-behind questionnaire in 2006 or 2008 ( N = 10, 827; M age = 68.38; SD = 9.81; range = 50–101). Participants reported on their own and both parents' educational attainment, subjective childhood financial situation, and financial difficulties in childhood at study entry and on well-being in 2006/2008. Linear regression was used to examine the association between offspring education, parental education, childhood SES and three aspects of well-being and self-beliefs: positive affect (e.g., positive emotions, optimism), negative affect (e.g., loneliness, hostility), and cognitive evaluation (e.g., life satisfaction). Participants with more education reported higher well-being (median β = 0.12). Parental educational attainment, subjective childhood SES, and a significant financial event during childhood were associated with more positive affect, less negative affect, and higher life satisfaction (median β = 0.05); these associations held controlling for offspring education. The educational and financial environment of childhood may hamper well-being into older adulthood; the offspring's own experiences and achievements do not completely attenuate the association with these aspects of the childhood environment. Highlights: The early life environment, including parental characteristics, may be associated with well-being across the lifespan Parent education is associated with higher well-being in older adulthood This association persists after accounting for the offspring's own level of education Early life factors have lasting associations with psychological functioning into older adulthood